Analisis Yuridis terhadap Pemagaran Laut di Pesisir Tangerang dalam Kerangka Hukum Laut Internasional - Rizca Aulia Ambarsari P.M; Syadifa Mesya Putri; Ernawati Ernawati; Sintong Arion Hutapea (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The phenomenon of sea fencing in Tangerang's coastal areas has sparked various debates from legal, social and environmental perspectives. This action raises questions regarding compliance with the principles of international law of the sea, particularly the 1982 United Nations Convention on the Law of the Sea (UNCLOS), which regulates public access rights to waters. In the context of national law, regulations such as Law No. 32/2014 on Maritime Affairs and Law No. 1/2014 on the Management of Coastal Areas and Small Islands emphasize that public access to the sea must be managed in a fair and sustainable manner. This research aims to examine the juridical aspects of sea fencing using the approaches of international law of the sea and Indonesian national law. The method used is a literature study by analyzing various legal sources, scientific journals, and similar case studies in other countries. Descriptive-analytical analysis was conducted to assess the conformity of sea fencing with UNCLOS principles as well as its impact on the rights of coastal communities and the environment. The results of the study show that sea fencing in coastal Tangerang has the potential to violate the principles of UNCLOS 1982 and harm coastal communities who depend on the sea as a source of life. In addition, this action also risks causing ecological impacts that can disrupt the balance of the coastal environment. Therefore, stricter regulations and effective supervision are needed to ensure that marine area utilization policies remain in line with international and national law and do not harm the public interest.